Structure-Induced Dynamics of Erythrocyte Aggregates by Microscale Simulation - Tong Wang; Zhongwen Xing; Dingyu Xing (Journal of Applied Mathematics)
Erythrocyte aggregation and dissociation play an important role in the determination of hemodynamical properties of blood flow in microcirculation. This paper intends to investigate the adhesion and dissociation kinetics of erythrocytes through computational modeling. The technique of immersed boundary-fictitious domain method has been applied to the study of erythrocyte aggregates traversing modeled stenotic microchannels. The effects of stenosis geometry, cell membrane stiffness, and intercellular interaction strength on aggregate hemodynamics including transit velocity are studied. It is found that the width of the stenosis throat and shape of stenosis have a significant influence on the dissociation of the aggregates. Moreover, horizontally orientated erythrocyte aggregates are observed to dissociate much easier than their vertical counterparts under the same simulation conditions. Results from this study contribute to the fundamental understanding and knowledge on the biophysical characteristics of erythrocyte aggregates in microscopic blood flow, which will provide pathological insights into some human diseases, such as malaria.